Effect of silica filler on viscosity and adhesion properties of natural rubber based adhesive - Poh B T; Ahmad L (Journal of Rubber Research, 2016)
Viscosity, tack, peel strength and shear strength of natural rubber-silica composite-based adhesive were studied using gum rosin as the tackifying resin. The silica content varied from 0-50 phr. Toluene and poly(ethylene terephthalate) (PET) were used as the solvent and coating substrate respectively. Viscosity of the adhesive was measured by a Brookfield Viscometer whereas tack, peel strength and shear strength were determined by a Lloyd Adhesion Tester operating at 30 cm/min. Results indicate that viscosity increases steadily with silica loading due to the concentration effect of the filler. However, tack, peel strength and shear strength increase with silica content up to 20 phr silica loading, after which the adhesion properties decrease with further addition of silica. This observation is attributed to the culmination of wettability and cohesive strength at 20 phr of silica loading. In all cases, tack, peel strength and shear strength increase with coating thickness of the adhesive.
Source Year: 2016
Keywords: Adhesive; Natural rubber; Peel; Shear; Silica